A General Mechanism for Achieving Circular Dichroism in a Chiral Plasmonic System. Issue 11 (30th September 2018) - Qu, Yu; Zhang, Yu; Wang, Fei; Li, Hui; Ullah, Hamad; Aba, Tudahong; Wang, Yongkai; Fu, Tong; Zhang, Zhongyue
Abstract: Chiral plasmonic (CP) systems are shown to exhibit effectual circular dichroism (CD). A general mechanism based on the Jones matrix for predicting the CD signal of CP systems is proposed. Considering the near‐field coupling of adjacent layers of trilayer CP systems, the coupling matrix, which shows the relevance of the coupling status to the relative position of the adjacent layers, is analytically derived under the framework of the transfer matrix method. To prove the coupling matrix, a trilayer system is designed, and the optical properties of the relevant system arrays are simulated using the finite‐element method. The fitting functions of the simulated CD signals at resonant wavelengths are consistent with the theoretical formulas. The proposed mechanism facilitates an understanding of the underlying physical mechanism of CD and offers a design principle for fabrication of CP systems that are applicable to biosensing. Abstract : To selectively control the elements of linear polarization for different responses, a trilayer chiral plasmonic system is designed to achieve circular dichroism (CD). Considering the near‐field coupling effect, the formula of the system is demonstrated by deducing the coupling matrix based on the transfer matrix method. The fitting formulas of the simulated CD signals are consistent with the theoretical calculations.